Forest road and fuelbreak siting with respect to reference fire intensities - Eastaugh, C.S.; Molina, D.M. (Forest Systems, 2012)
Forest roads and permanent fuelbreaks are an important part of fire suppression infrastructure, but due to maintenance and environmental costs many forest agencies seek to reduce the extent of these networks. The question of which roads should be retained or where fuelbreaks should be established is contentious, and few quantified methods exist to aid management decisions. This study uses GIS procedures and develops a metric for road network vulnerability, which may be used to determine the relative effectiveness of a road network or a particular fuelbreak as a fire control line. The method constructs ‘reference fire’ intensities, and compares the fire intensity at roadsides or fuelbreaks with the overall forest average. In the case study area in Victoria’s Central Highlands (southeast Australia), average fire intensities on the forest road network are found to closely match the forest average, indicating that roads in their current locations are not skewed towards more dangerous parts of the forest. The fuelbreak network however is likely to face fire intensities substantially greater than those in the average forest area.